Application of Toxoplasma gondii-specific SAG1, GRA7 and BAG1 proteins in serodiagnosis of animal toxoplasmosis - Qi, Tongsheng; Ai, Jingkai; Sun, Yali; Ma, Hejia; Kang, Ming; You, Xiaoqian; Li, Jixu (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasmosis is a zoonotic disease caused by the obligate intracellular protozoan parasite T. gondii which is widely prevalent in humans and animals worldwide. The diagnosis of toxoplasmosis and distinguishing acute or chronic T. gondii infections have utmost importance for humans and animals. The TgSAG1, TgGRA7, and TgBAG1 proteins were used in the present study to develop the serological rSAG1-ELISA, rGRA7-ELISA and rBAG1-ELISA methods for the testing of T. gondii specific IgG and IgM antibodies and differentiating acute or chronic toxoplasmosis in 3733 animals, including Tibetan sheep, yaks, pigs, cows, cattle, horses, chickens, camels and donkeys from the Qinghai-Tibetan Plateau. The ELISA tests showed that the overall positivity of IgG antibody was 21.1% (786/3733), 15.3% (570/3733) and 18.2% (680/3733) for rSAG1-, rGRA7- and rBAG1-ELISA, respectively, and the positivity of IgM antibody was 11.8% (439/3733), 13.0% (486/3733) and 11.9% (442/3733) for rSAG1-, rGRA7- and rBAG1-ELISA, respectively. A total of 241 animals (6.5%) positive for all rSAG1-, rGRA7- and rBAG1-IgG were found in this study, and the 141 animals (3.8%) tested were anti-T. gondii IgM positive in all three ELISAs. Moreover, the 338, 284 and 377 animals were IgG positive in rSAG1 + rGRA7-, rBAG1 + rGRA7- and rSAG1 + rBAG1- ELISAs respectively, and the 346, 178 and 166 animals in rSAG1 + rGRA7-, rBAG1 + rGRA7- and rSAG1 + rBAG1-ELISAs were IgM positive respectively. The results confirmed that the application of SAG1, GRA7, and BAG1 recombinant antigens could successfully be used in the detection of specific IgG and IgM antibodies for distinguishing between acute or chronic T. gondii infections. It is inferred that the forms in which current animal species in the plateau area were infected with T. gondii, and the period of infection or the clinical manifestations of the current infections may be different. The present study provides substantial clinical evidence for the differential diagnosis of toxoplasmosis, and the classification of acute and chronic T. gondii infections.